(untitled) (International Journal of Mathematics and Physics, 2018)
Abstract. In this paper, the properties of complex plasma and the manipulation of plasma-dust layer in high-frequency discharge with an additional alternative phase have been investigated. The computer simulation of the high-frequency capacitive discharge has been carried out under the influence of an additional alternative phase on the basis of the particle-in-cell and Monte Carlo (PIC / MCC) methods. The parameters describing the kinetic and transport properties (density and temperature of electrons, electron and ion heating rates) of complex plasma of high-frequency capacitive discharge have been obtained. The charging processes of dust particles, the forces acting on dust particles, as well as the equilibrium positions of the dust particles in the plasma have been studied. A method for manipulating particles of micro and nano sizes in a low-temperature complex plasma has been developed. The results have shown that the dust charge can be tuned by the properties of the excitation waveform and in connection with it we have suggested that the dust component of the plasma can be heated through a variation of the excitation waveforms via a mechanism similar to second-order Fermi acceleration. G M T Английский Испанский Итальянский Казахский Китайский Трад Китайский Упр Корейский Русский Турецкий Французский Английский Испанский Итальянский Казахский Китайский Трад Китайский Упр Корейский Русский Турецкий Французский Звуковая функция ограничена 200 символами Настройки : История : Обратная связь : Donate Закрыть